The effect of pretreatment choice on cellulosic ethanol production from sugarcane straw: An insight into environmental impact profile and GHG emissions mitigation potential in Brazil - Nogueira, Guilherme Pessoa [UNESP]; Hernandes, Thayse Aparecida Dourado; Petrielli, Gabriel Palma; Chagas, Mateus Ferreira; Junqueira, Tassia Lopes [UNESP]; McManus, Marcelle; Leak, David; Franco, Telma Teixeira; Dias, Marina Oliveira de Souza; Cavaliero, Carla Kazue Nakao [UNESP] (Elsevier, 2023)
The exploration of residual lignocellulosic biomass for biofuel production is crucial to achieve significant greenhouse gas (GHG) emissions mitigation within the following decades, translating to diminished agricultural environmental impact and land-use change dynamics. On the other hand, cellulosic ethanol production pathways are typically resource-intensive, in energy and chemical terms, which directly influence its carbon intensity. Pretreatment choice, to this end, is key, since it dictates the overall process performance and yield, and may include crucial flows, under the life-cycle perspective, such as solvents and other chemicals. This work, then, aims to evaluate the effect of pretreatment choice, namely hydrothermal (HT), steam explosion (SE), and alkaline (AK), in the technical and environmental performance of cellulosic ethanol production from sugarcane straw (SCS), extending this analysis to the final GHG emissions mitigation potential for gasoline and fossil-generated electricity substitution, under the Brazilian context in São Paulo. Results show that, while AK provided the highest ethanol yield, this pretreatment option gave the lowest electricity generation surplus, and its sodium hydroxide usage was identified as an important environmental hotspot in most impact categories, which narrowed down its GHG emission mitigation gap for gasoline substitution. HT and SE presented similar ethanol and electricity yields, with SE being the most balanced option in terms of productivity and environmental impact profile. By selecting the SE route, all of the available SCS in São Paulo could be converted into 10% of the Brazilian annual ethanol production, and mitigate 5.4 MtCO2e of gasoline emissions, 15% of the Brazilian Biofuel Policy (RenovaBio) target for 2022.
Keywords: Biorefinery design and simulation; Cellulosic ethanol; Life cycle assessment; Pretreatment; Sugarcane straw